Investigation of Various Diseases Occurred in Poultry and Management Strategies for Eradication - patil, Sunil; I.L, Chhanwal (International Journal of Engineering and Technology, 2018)
Poultry plays a significant role in the Indian economy. Around 60 billion chickens are raised per annum as a basis of food for both their eggs and meat. Poultry meat is in significant source of minerals, protein and various vitamins to balance the diet of human. Broiler farming is an important source of family income depending on size of the farm. Chicken farming in Commercial way is the most fruitful business in India and all around the world. Proper farm management practice and care of birds will result in decent profit in a short span of time. In this paper, we are discussing various diseases caused to poultry hen and their preventing or treating methods. Our results shows that some of disease cannot be cured and only it can be prevented. Spreading of disease with the help of contaminated equipment and infected poultry trade is measured as foremost means of spreading of poultry disease. In some countries migratory birds have also been foremost means of spreading of poultry disease like highly pathogenic viruses.Â